Predictors of Failed Conscious Sedation in Patients Undergoing an Outpatient Colonoscopy and Implications for the Adenoma Detection Rate - Cassell, Benjamin E. (Sci Rep, 2020)
Guidelines to triage patients to conscious sedation (CS) or monitored anaesthesia care (MAC) for colonoscopy do not exist. We aimed to identify the CS failure rate, predictors of failure, and its impact on the adenoma detection rate (ADR). Strict (based on patient experience) and expanded (based on doses of sedative medications) definitions of CS failure were used. Patient and procedure-related variables were extracted. Multivariable logistic regression identified predictors for CS failure and the ADR. Among 766 patients, 29 (3.8%) and 175 (22.8%) patients failed CS by strict and expanded definitions, respectively. Female gender (OR 3.50; 95% CI: 1.37–8.94) and fellow involvement (OR 4.15; 95% CI: 1.79–9.58) were associated with failed CS by the strict definition. Younger age (OR 1.27, 95% CI: 1.07–1.49), outpatient opiate use (OR 1.71; 95% CI 1.03–2.84), use of an adjunct medication (OR 3.34; 95% CI: 1.94–5.73), and fellow involvement (OR 2.20; 95% CI: 1.31–3.71) were associated with failed CS by the expanded definition. Patients meeting strict failure criteria had a lower ADR (OR 0.30; 95% CI: 0.12–0.77). Several clinical factors may be useful for triaging to MAC. The ADR is lower in patients meeting strict criteria for failed CS.